Strategi Komunikasi Perwakilan BKKBN Provinsi Banten Dalam Pengendalian Penduduk di Provinsi Banten - Ega Ernayanti; Iman Mukhroman; Ail Muldi (Magister Komunikasi Universitas Sultan Ageng Tirtayasa, 2020)
The background of this research is that the population in Banten Province ranks 5th most populous in Indonesia reaching 12,203,148 people with the 3rd fastest population growth rate in Indonesia reaching 2.07% during 2015-2016. The progress of human development in Banten in 2017 experienced a slowdown marked by the growth of HDI (Human Development Index) which reached 0.65%, lower than the growth in 2016 which reached 0.98%. HDI is an important indicator to measure success in an effort to build quality of life for people (people / residents). This study aims to determine the communication strategy used by the Banten Province BKKBN Representative in controlling the population in Banten Province. This study uses a case study method and a qualitative approach to the Concept of Development Strategy according to the Academy for Educational Development (AED) 1985 and the theory of preparation of action by John Greene. The strategy used by the Banten Province BKKBN Representative is a strategy that is relevant to the theory of preparation of action, this theory of the preparation of actions examines the way we organize knowledge in the mind and use it to form a message. Penelitian ini dilatarbelakangi dari jumlah penduduk di Provinsi Banten menduduki peringkat terpadat ke-5 di Indonesia mencapai 12.203.148 jiwa dengan Laju Pertumbuhan Penduduk tercepat ke-3 di Indonesia mencapai 2,07 % sepanjang tahun 2015-2016. Kemajuan pembangunan manusia di Banten pada tahun 2017 mengalami perlambatan ditandai dengan pertumbuhan IPM (Indeks Pembangunan Manusia) yang mencapai 0,65 %, lebih rendah dibandingkan pertumbuhan tahun 2016 yang mencapai 0,98 %. IPM merupakan indikator penting untuk mengukur keberhasilan dalam upaya membangun kualitas hidup manusia (masyarakat/penduduk). Penelitian ini bertujuan untuk mengetahui strategi komunikasi yang digunakan Perwakilan BKKBN Provinsi Banten dalam pengendalian penduduk di Provinsi Banten. Penelitian ini menggunakan metode studi kasus dan pendekatan kualitatif dengan Konsep Strategi Pembangunan menurut Academy for Educational Development (AED) 1985 dan teori penyusuan tindakan oleh John Greene. Strategi yang digunakan Perwakilan BKKBN Provinsi Banten merupakan strategi yang relevan dengan teori penyusunan tindakan, teori ini penyusunan tindakan menguji cara kita mengatur pengetahuan dalam pikiran dan menggunakannya untuk membentuk sebuah pesan.